The Effect of Work Experience and Job Training on Employee Productivity with Motivation as an Intervening Variable at PT. Pratama Putra Transportation: Pengaruh Pengalaman Kerja dan Pelatihan Kerja Terhadap Produktivitas Karyawan dengan Motivasi sebagai Variabel Intervening Pada PT. Pratama Putra Transportation - Rosada, Siti Imroatun; Ubaidillah, Hasan (Indonesian Journal of Innovation Studies, 2022)
This study aims to examine the effect of work experience and job training on employee productivity with motivation as an intervening variable. The approach used in this research is a quantitative approach. The population in this study were all employees of PT. PRATAMA PUTRA TRANSPORTATION in the driver and co-driver section, totaling 54 employees. The sampling technique used the total sampling method (saturated sampling). The sample in this study were 54 employees at PT. PRATAMA PUTRA TRANSPORTATION. The data used in this study are questionnaire data and data sourced from PT. PRATAMA PUTRA TRANSPORTATION. Data collection techniques using questionnaires, interviews, observations, and documentation. Data analysis using SmartPLS 3.2.8 Software. The results obtained from the path analysis showed that work experience had a significant effect on employee productivity, job training had a significant effect on employee productivity, work experience had a significant effect on motivation, job training had a significant effect on motivation, motivation had a significant effect on employee productivity, work experience had a significant effect on motivation. significant effect on employee productivity through motivation as an intervening variable, and job training has a significant effect on employee productivity through motivation as an intervening variable. Keywords: work experience, job training, employee productivity, and motivation.